PERANCANGAN KAMPANYE SOSIAL TERTIB DAN AMAN BERLALU LINTAS - Hendika Setiabudi; Heri Iswandi; Bobby Halim (Besaung : Jurnal Seni Desain dan Budaya, 2016)
Palembang city is currently experiencing rapid progress in terms of transportation. It is marked with the number of new infrastructure such as the LRT and road construction. However, there are several issues that still often occurs in the highway of Palembang city, these concerns are traffic violations and unsafe driving behavior in this context made by motorcyclists. Therefore, the Design Of Social Campaign Orderly and Safely Traffic Behaviour Based On Safety Riding is designed with the aim to raise awareness and urge the public about the importance of obeying traffic laws and drive safely. Media campaigns were containing various information regarding the traffic order, is designed in such a way without losing the factual aspects of the media as well as easy to be digested by the public.Keywords: Social Campaign, Safety Riding, Traffic